2007
DOI: 10.1128/mcb.02112-06
|View full text |Cite
|
Sign up to set email alerts
|

ΔNp73 Modulates Nerve Growth Factor-Mediated Neuronal Differentiation through Repression of TrkA

Abstract: p73, a member of the p53 family, expresses two classes of proteins: the full-length TAp73 and the Nterminally truncated ⌬Np73. While TAp73 possesses many p53-like features, ⌬Np73 is dominant negative towards TAp73 and p53 and appears to have distinct functions in tumorigenesis and neuronal development. Given its biological importance, we investigated the role of ⌬Np73 in nerve growth factor (NGF)-mediated neuronal differentiation in PC12 cells. We show that overexpression of ⌬Np73␣ or ⌬Np73␤ inhibits NGFmediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 54 publications
1
17
0
Order By: Relevance
“…We also showed that TAp73 physically interacted with HDAC1 (Fig. 4, G and H, lanes 3), consistent with previous report (57). Next, we determined whether HDAC1 knockdown would affect the association between TAp73 and Hsp90.…”
Section: Hdac1 Knockdown Induces Hyperacetylation Of Hsp90 and Disrupsupporting
confidence: 74%
“…We also showed that TAp73 physically interacted with HDAC1 (Fig. 4, G and H, lanes 3), consistent with previous report (57). Next, we determined whether HDAC1 knockdown would affect the association between TAp73 and Hsp90.…”
Section: Hdac1 Knockdown Induces Hyperacetylation Of Hsp90 and Disrupsupporting
confidence: 74%
“…Cell culture and cell line generation RKO, MCF7, HCT116, p21-null HCT116, and p53-null HCT116 cells were cultured in DMEM (Invitrogen) supplemented with 10% fetal bovine serum (Hyclone) as previously described (Zhang and Chen 2007). p53…”
Section: Plasmidsmentioning
confidence: 99%
“…Western blot analysis was performed as previously described (Zhang and Chen 2007). Cell lysates suspended in 23 SDS sample buffer were resolved by SDS-PAGE, transferred to a nitrocellulose membrane, and probed with the indicated antibodies.…”
Section: Western Blot Analysis and Immunoprecipitationmentioning
confidence: 99%
See 1 more Smart Citation
“…RKO, MCF7, HCT116, H1299, and SW480 cells were cultured as described (Zhang and Chen 2007). Primary MEFs were cultured in DMEM supplemented with 10% fetal bovine serum.…”
Section: Cell Culturementioning
confidence: 99%